USING CLOUD TECHNOLOGIES AND BIG DATA TO OPTIMIZE THE DIGITAL TRANSFORMATION OF CHILDREN'S HEALTH CAMPS IN UZBEKISTAN: COMPREHENSIVE ASSESSMENT AND IMPLEMENTATION STRATEGY (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This research paper examines the issue of digitization of children's health camps in the Republic of Uzbekistan, sheds light on the integration of cloud technologies and big data to ensure a comprehensive transformation. In the context of a rapidly developing digital landscape, optimizing the provision of medical services to the country's youth is of paramount importance. This study includes a multifaceted approach, bringing together areas such as information technology, health and public service management. In order to assess the potential of cloud technologies and big data, the study carefully analyzed the existing structure of children's health camps. It takes a thorough look at data management, resource allocation, and performance monitoring to assess the efficiency and effectiveness of the existing system. In addition, the study examines the ethical aspects related to digital transformation, with a focus on data security, privacy, and fairness. The results of the study clarify the benefits, challenges and Opportunities to use cloud technologies and big data in the context of children's health camps. Harnessing the power of these innovative technologies will improve the quality of services, resource efficiency, and the overall well-being of campers. This work is intended to be a comprehensive guide for policymakers, health administrators, and technologists involved in the modernization of children's health camps, not only in Uzbekistan, but also as a potential model for other regions seeking to use advanced technologies to improve youth health care.